Spring loaded plunger attachment for retention of removable partial denture: a case report - Awang, Raja Azman Raja; Arief, Erry Mochamad; Hassan, Akram (Penerbit USM, 2008)
Since the establishment of implant in dentistry, the use of removable partial denture in replacing missing teeth apparently becomes less popular. The situation is made worse by the renowned limitations of removable partial denture. One of the obvious limitations of removable partial denture, especially in replacing missing anterior teeth is the unsightly view of metal used for retentive clasp. This case report describes the use of spring loaded plunger attachments as an alternative way to achieve retention and at the same time improving the aesthetic of the prosthesis.